2015
DOI: 10.1111/bjh.13760
|View full text |Cite|
|
Sign up to set email alerts
|

Lymphotoxin-β receptor in microenvironmental cells promotes the development of T-cell acute lymphoblastic leukaemia with cortical/mature immunophenotype

Abstract: SummaryLymphotoxin-mediated activation of the lymphotoxin-b receptor (LTbR; LTBR) has been implicated in cancer, but its role in T-cell acute lymphoblastic leukaemia (T-ALL) has remained elusive. Here we show that the genes encoding lymphotoxin (LT)-a and LTb (LTA, LTB) are expressed in T-ALL patient samples, mostly of the TAL/LMO molecular subtype, and in the TEL-JAK2 transgenic mouse model of cortical/mature T-ALL (Lta, Ltb). In these mice, expression of Lta and Ltb is elevated in early stage T-ALL. Surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 56 publications
5
27
0
Order By: Relevance
“…In contrast with these data, we found that loss of a single Foxn1 allele hindered both the onset of spontaneous TEL-JAK2-induced leukemia/lymphoma and the thymic expansion of leukemic cells in recipient mice. Since leukemogenesis in TJ2-Tg mice is initiated in the thymus (33,37) and only TECs express Foxn1, we conclude that the delayed leukemogenesis in heterozygotes is caused by FoxN1-mediated defects dependent on these cells. Foxn1 haploinsufficiency was shown to cause a moderate reduction in thymic weight of pre-puberty mice (under 5 weeks) of different outbred and inbred strains (28,44,45).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…In contrast with these data, we found that loss of a single Foxn1 allele hindered both the onset of spontaneous TEL-JAK2-induced leukemia/lymphoma and the thymic expansion of leukemic cells in recipient mice. Since leukemogenesis in TJ2-Tg mice is initiated in the thymus (33,37) and only TECs express Foxn1, we conclude that the delayed leukemogenesis in heterozygotes is caused by FoxN1-mediated defects dependent on these cells. Foxn1 haploinsufficiency was shown to cause a moderate reduction in thymic weight of pre-puberty mice (under 5 weeks) of different outbred and inbred strains (28,44,45).…”
Section: Discussionmentioning
confidence: 79%
“…However, thymi from TJ2-Tg;Foxn1 +/nu mice displayed a significantly lower percentage of CD8 + CD25 + cells than TJ2-Tg;Foxn1 +/+ thymi (7.8-fold difference; Figure 3F). At this age, leukemic cells are detectable mainly in the thymus (33). Although low percentages of CD8 + CD25 + cells could be detected in the blood, bone marrow and spleen of some mice, those were not significantly different among Foxn1 genotypes ( Figure 3F and not shown).…”
Section: Foxn1 Haploinsufficiency Delays the Onset Of Tel-jak2-inducementioning
confidence: 88%
See 2 more Smart Citations
“…Errors have been identified in the Figure 1 text citations of Fernandes et al () on page 742, column 1.…”
mentioning
confidence: 99%